PENINGKATAN MOTIVASI BELAJAR SISWA SMA DENGAN PENDEKATAN KONTEKSTUAL MENGGUNAKAN MEDIA SIMULASI VIRTUAL PhET DI SMAN 10 PEKANBARU - Safitri, Lisa Andriani; Nasir, Muhammad; ', Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This research aimed to describe and find out the improvement of the students motivation learning by using media simulated virtual PhET through contextual approach at SMAN 10 Pekanbaru. This type of research is a true-experimental, with the pretest posttest- control grup design. The subject of this research is students class VIII at SMPN 34 Pekanbaru, total of 96 students as divide into two class, experimental class and control class. The data in this research is a score of motivation before and after learning physics by implementation of media simulated virtual PhET through contextual approach approach at SMAN 10 Pekanbaru and analysis of the data uses descriptive analysis. Then, measured the improvement of the students motivation by The result of this research using SPSS 23. Score motivation of students at experimental class in high category and increase in the middle category with score 5,13, and the control class in the low category with score 3,24. Therefore, it can be concluded that the using of media simulated virtual PhET through contextual approach able to improve the motivation of students at SMAN 10 PekanbaruKey Words: Media simulated virtual PhET, contextual learning, Motivation.